The effects of labour market reforms upon unemployment and income inequalities: an agent based model - Dosi, Giovanni; Pereira, Marcelo; Roventini, Andrea; Virgillito, Maria Enrica (Paris, 2016)
"This paper is meant to analyse the effects of labour market structural reforms by means of an agent-based model. Building on Dosi et al. (2016b) we introduce a policy regime change characterized by a set of structural reforms on the labour market, keeping constant the structure of the capital- and consumption-good markets. Confirming a recent IMF report (Jaumotte and Buitron, 2015), the model shows how labour market structural reforms reducing workers’ bargaining power and compressing wages tend to increase (i) unemployment, (ii) functional income inequality, and (iii) personal income inequality. We further undertake a global sensitivity analysis on key variables and parameters which confirms the robustness of our findings."